Development and Validation of a Process Skill Rating Scale for Assessing Practical Competencies in Motor Vehicle Mechanic Work in Technical Colleges in Bayelsa State, Nigeria - Jacob (Journal of Research in Industrial Technology and Educational Studies, 2026)
This study examined the internal consistency of a developed practical skills assessment instrument designed for TVET students in fault diagnoses and repairs in petrol engine maintenance in Bayelsa State, Nigeria. An instrumentation research design was employed for the study, which was conducted in Bayelsa State, Nigeria. The study population consisted of 72 students offering Motor Vehicle Mechanic Work from three technical colleges. Data were collected using a Process Skill Rating Scale containing 32 test items related to Service Station Mechanic Work. and petrol engine maintenance. The items were developed through a task analysis questionnaire and subsequently subjected to expert review and validation by three experts. Findings revealed that all 32 process skill test items were appropriate for assessing practical competencies and demonstrated a high level of internal consistency. The instrument achieved a reliability coefficient of 0.87, indicating strong reliability and confirming its suitability for inclusion in practical skills assessment. Based on the findings, the study recommended that the National Business and Technical Examinations Board (NABTEB) integrate the developed process skill test items into its certification examinations for students of Motor Vehicle Mechanic Work at the National Technical Certificate (NTC) level. The study further recommended that the West African Examinations Council (WAEC) and the National Examinations Council (NECO) adopt the Process Skill Rating Scale as an assessment tool for evaluating practical competencies in Motor Vehicle Mechanic Work and Automobile Technology programmes in Nigeria.
Keywords: Process skills rating; Practical Skills Assessment; Motor Vehicle Mechnic Woek; petrol engine maintenance